Pengantar Manajemen Sumber Daya Manusia - Husni Pasarela (CiDEA Journal, 2023)
Human resources as one of the resources in an organization play an important role in the successful achievement of organizational goals. Human resources use other resources owned by the organization in order to achieve goals. Even sophisticated technological machines will be meaningless if the human resources running them are not qualified to work on them. Likewise with information resources. No matter how good and complete the information received by the organization, it will not mean anything, if the quality of existing human resources is not able to translate it into information that is useful for the development and progress of the organization. Human resource management is the process of planning, organizing, implementing and controlling towards human resources in the organization to achieve goals effectively and efficiently. The management functions applied in human resource management consist of, (1) planning, (2) organizing, (3) directing. ), and (4) controlling. The operational functions carried out by human resource management are, (1) procurement, (2) development, (3) compensation, (4) integration, (5) maintenance, and (6) termination of employment (separation). One of the important activities carried out in human resource management, especially in the planning function, is job analysis. By analyzing a job, it will be known what tasks will be carried out in that job, what competencies must be mastered by the human resources who will occupy that position.